PARTICIPATION IN STRATEGIC PLANNING: IMPLICATIONS FOR ACADEMIA - Armia, Saed (Universitas Muhammadiyah Aceh, 2011)
Well design of strategic planning is highly vital for higher education institution. This strategic planning becomes important foundation of how the universities/colleges leaders move their organization forward and on the track. Therefore, one of important thing needed to be considered is engagement of important stake holders in formulation strategic planning such as lecturers, students, administration staffs are important groups that determine institution sustainability. To implement this process is not easy way out because each group has different interests that must be synergize to succeed strategic planning implementation. Although researches in this area are still limited, but one of important consideration we draw that it is important to have strong commitment support of top campus management to create an adaptive strategic plan. Keywords: Strategic planning, constituent engagement, and academia REFERENCES Alfred, R.L. (2006). Managing the big picture in colleges and universities: From tactics to strategy. Westport, CT: Praeger Publishers. Allen, D.K. (2003). Organisational climate and strategic change in higher education: Organisational insecurity. Higher Education, 46, 61-92. Bryson, J.M. & Bromley, P. (1993, July). Critical factors affecting the planning and implementation of major projects. Strategic Management Journal, 14(5), 319-337. Kezar, A. (2006, September/October). Redesigining for collaboration in learning initiatives: An examination of four highly collaborative campuses. The Journal of Higher Education, 77(5), 804-838. Kotler, P. & Murphy, P.E. (1981, September/October). Strategic planning for higher education. The Journal of Higher Education, 52(5), 470-489. Lerner, A.L. (1999). A strategic planning primer for higher education. Retrieved November 11, 2008, from California State University, College of Business Administration and Economics Web site: http://www.atlm.edu/irpa/publications/Strategic_Planning_Primer.pdf Marcus, L.R. (1999). The micropolitics of planning. The Review of Higher Education,23(1), 45-64. Oswald, S.L, Mossholder, K.W. & Harris, S.G. (1994, July). Vision salience and strategic involvement: Implications for psychological attachment to organization and job. Strategic Management Journal, 15(6), 477-489. Philpott, J.L & Strange, C. (2003, January/February). On the road to Cambridge: A case study of student affairs in collaboration. The Journal of Higher Education, 74(1), 77-95. Rutgers University (2007). Strategic planning in higher education: A guide for leaders. Retrieved November 11, 2008, from Rutgers University, Center for Organizational Development and Leadership Web site: http://www.odl.rutgers.edu VanWagoner, R.J. (2001). A framework for academic planning: Engaging faculty in strategic dialogue (Report No. JC 010 508). Omaha, NE: Metropolitan Community College. (ERIC Document Reproduction Service No. ED454919).